The Relationship of Sleep Duration, Excersise Habits, Physical Activity and Eating Frequency to Nutritional Status of Students of SMAN 22 Surabaya During The Pandemic Covid-19 - Reza Farhana Zuhar (Media Gizi Kesmas, 2022)
Background: The COVID-19 pandemic that has spread throughout the country has caused changes in behavior patterns due to social restrictions. This has resulted in activities outside the home and in open spaces being limited and even abolished and replaced with online activities (in the network). Students who usually take part in teaching and learning activities and do sports and extracurricular activities that they like at school turn into online activities at home. Teenagers cannot socialize with their friends and their space becomes limited during the Covid-19 pandemic so they tend to play social media and get a lot of sleep disorders and experience depression. In addition to changing activities, adolescents' eating patterns and sleep duration also change due to changes in daily routines. This condition affects the nutritional status of adolescents.Objectives: This study was conducted to analyze the relationship between sleep duration, exercise habits, physical activity and eating frequency with the nutritional status of the students of SMAN 22 Surabaya.Method: This research is an analytical observational study conducted at SMA Negeri 22 Surabaya with 170 respondents aged 15-17 years. The measurements taken included the respondent's nutritional status, anthropometry, sleep duration, exercise habits, physical activity and adolescent eating frequency during the pandemic. Statistical analysis used to test the hypothesis of this study using the chi-square test.Result: The nutritional status of non-obese as many as 94 students, and nutritional status of obesity as many as 76 students. Respondents with short sleep duration were 53 students, adequate sleep duration was 105 students, and long sleep duration was 12. Respondents with regular exercise habits were 45 students, and non-routine exercise habits were 125 students. Respondents with light physical activity were 75 students, moderate physical activity was 49 students, and high physical activity was 45 students. Respondents with low eating frequency were 113 students, 37 students had moderate eating frequency and 20 students had high meal frequency.Conclution: nutritional status is related to sleep duration, exercise habits, and eating frequency during the pandemic.